Tourism Management with the Concept of Green Economy to Increase People’s Economic Income During the Covid-19 Pandemic - Maulana, Ilham Nur Hanifan; Nashihah, Durratun; Wardah, Tasya Fiane (Proceedings of International Conference of Graduate School on Sustainability, 2022)
The tourism sector was the hardest hit during the Covid-19 outbreak following the decrease in people’s income, generally 50-75%. Enhancing tourism management is needed, especially for local destinations managed by surrounding communities, such as the island of Bawean. The latest report shows a significant downturn in international tourist visits, which is the primary visitor in Bawean, to 70% in 2020. This article aims to give a clear vision for reformulating regional tourism management by strengthening existing potential through a sustainable view within the green economy. Although the green economy is a relatively new concept, it has a big prospective impact as an equal way to implement economics for people and the planet. This research is included in the type of research that uses a qualitative-exploratory approach, which uses a continuous and intertwined literature review research design. From Bawean island, we explore the management of tourism villages through community-based leadership. We could see that Bawean can carry out a comprehensive green economy in the future. That’s why we suggested an enlargement of attractions, amenities, access, and ancillary services in the tourism village management based on empowering local communities and following the flow of nature. Keywords: Tourism Management, Concept of Green Economy, Economic Income during the Covid-19 Pandemic